LIBRARIANS’ EMERGING SKILLS FOR THE 21ST CENTURY INFORMATION SERVICE DELIVERY IN ACADEMIC LIBRARIES IN NIGERIA (NAU Journal of Library and Information Science, 2022)
Rapid technological advancement of the 21st century has changed the way information is created, packaged and disseminated. It has also affected the information seeking behavior of users of information as well as library users. Librarians by their training and profession are at the centre of this evolution. Expectedly, librarians of the 21st Century should envisage these changes, plan for it and strategize in order to remain relevant in the teaching, learning and research of the university. The integration of ICT in library services has changed the work schedule of the librarian. This means that the 21st century librarian will have to be armed with relevant skills that will enhance the provision of library services to meet client‘s changing information needs. This paper discussed the changing role of the academic librarian and the skills he should possess to remain relevant in the emerging technology.
Keywords: Information Technology; Librarians Skills; Academic Libraries; 21st Century